1999
DOI: 10.1103/physrevb.59.1016
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic coupling in the weak ferromagnetCuF2

Abstract: CuF 2 is known to be an antiferromagnetic compound with a weak ferromagnetism due to the anisotropy of its monoclinic unit cell ͑Dzialoshinsky-Moriya mechanism͒. We investigate the magnetic ordering of this compound by means of ab initio periodic unrestricted Hartree-Fock calculations and by cluster calculations which employ state-of-the-art configuration interaction expansions and modern density functional theory techniques. The combined use of periodic and cluster models permits us to firmly establish that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 41 publications
1
38
0
Order By: Relevance
“…However, it is shown that in some cases the mappings between the Ising and the Heisenberg Hamiltonians justify the extracting of magnetic coupling constants with the Ising Hamiltonian. [2][3][4][5] For a general spin dimer it is proved that the highest spin (HS) state is an eigenstate of both the Heisenberg and the Ising Hamiltonians with the same eigenvalue and that the eigenvalue of the Ising Hamiltonian for the broken symmetry (BS) spin state is the same as the expectation value of the Heisenberg Hamiltonian for the same BS spin state. 5 Since the Heisenberg Hamiltonian has not exactly been solved for dimensions above one, it is not possible to build a general mapping between the Heisenberg and the Ising Hamiltonians.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is shown that in some cases the mappings between the Ising and the Heisenberg Hamiltonians justify the extracting of magnetic coupling constants with the Ising Hamiltonian. [2][3][4][5] For a general spin dimer it is proved that the highest spin (HS) state is an eigenstate of both the Heisenberg and the Ising Hamiltonians with the same eigenvalue and that the eigenvalue of the Ising Hamiltonian for the broken symmetry (BS) spin state is the same as the expectation value of the Heisenberg Hamiltonian for the same BS spin state. 5 Since the Heisenberg Hamiltonian has not exactly been solved for dimensions above one, it is not possible to build a general mapping between the Heisenberg and the Ising Hamiltonians.…”
Section: Introductionmentioning
confidence: 99%
“…The cluster model contains a quantum-mechanical part and a proper representation of the rest of the crystal by means of a simple and convenient embedding procedure. As in previous researches, 14,52,53,62,[73][74][75][76][77][78][79][80] the quantummechanical part contains the two magnetic centers of interest and the anions in the proper coordination sphere. The final cluster models thus designed are Ni 2 O 11 and Ni 2 O 10 depending on whether the Ni-O-Ni magnetic path corresponds to an angle of 180°͑single bridge͒ or 90°͑double bridge͒.…”
Section: B Cluster Model Approachmentioning
confidence: 99%
“…25,60 Usually, the different broken symmetry solutions are found by doubling the unit cell in the appropriate direction. 25,26,37,61 However, in the case of LaMnO 3 there are several possible broken symmetry solutions within the primitive unit cell. Following the work of Su et al 29 we have chosen to study the four lowest broken symmetry solutions; this will permit a detailed comparison with the previous UHF calculations and allows us to isolate the important effects of the different hybrid functionals on their relative energies.…”
Section: Magnetic Ordering and Phasesmentioning
confidence: 99%
“…Notice that with this definition positive ͑negative͒ values of the magnetic coupling constant mean ferromagnetic ͑antiferromagnetic͒ interactions. Using the mapping procedure described in previous works 26,60,61 an overdetermined set of three equations and two unknowns is obtained. These are…”
Section: Magnetic Ordering and Phasesmentioning
confidence: 99%